Foot Sensitivity Increases in Diabetes Patients Who Are Given Range of Motion Exercise at Kabila Community Health Center : A Case Series - Falah, Fakhriatul; Luawo, Herman; Tambuwun, Gregevita; Ayuni, Qurrata (Poltekkes Kemenkes Gorontalo, 2024)
Background: Diabetes mellitus is a disease that always increases from year to year. Diabetes mellitus sufferers can experience various kinds of complications which can result in decreased body function, one of which is decreased foot sensitivity. Various efforts can be made to overcome this problem, one of which is the active range of motion (ROM) of the legs. Active foot ROM is a basic movement to increase foot sensitivity in diabetes mellitus sufferers.Purpose: Describe the effect of Range of Motion (ROM) in increasing foot sensitivity in diabetes mellitus sufferers.Methods: The study using descriptive qualitative design with case study approachResults: There was an increase in foot sensitivity score in the three informants. There was also reduction in neuropathy symptoms after undergoing range of motion therapy.Conclusion: Range of motion can be applied to patient with decrease of foot sensitivity so that quality of life of diabetic patient can be improved.